Lawrence and the “homeless soul” - Jane Costin (Études Lawrenciennes)
Beginning by exploring ideas of “home,” this article shows how Lawrence’s reaction to Zennor in Cornwall establishes that, at least for a while, this was a place Lawrence regarded as home. In examining what contributes to feelings of “home,” it will make reference to “The Cathedral” chapter in The Rainbow where Will’s soul is depicted as being “homeless” because it is challenged by ideas outside of the church. It will then contrast this with Lawrence’s reaction to such matters. It will explain how a particular aspect of Zennor during the time Lawrence lived there were its connections to Aleister Crowley and occult ideas - things that were outside the church and that questioned Lawrence’s thinking. It will then look at Lawrence’s interest in the occult around this period, which will lead to the suggestion that, for Lawrence, a place that made his soul feel “homeless” was a place that he felt “at home.”